The first national survey of antimicrobial use among dentists in Japan from 2015 to 2017 based on the national database of health insurance claims and specific health checkups of Japan - Ono, Akane (PLoS One, 2020)
PURPOSE: To counter the global health threat of antimicrobial resistance, effective antimicrobial stewardship programs are needed to improve antimicrobial use (AMU) among dentists in addition to physicians. This study aimed to investigate the nationwide epidemiology of AMU among Japanese dentists to facilitate the development of dentist-centered programs. METHODS: We conducted a retrospective population-based study using the National Database of Health Insurance Claims and Specific Health Checkups of Japan to analyze the AMU among Japanese dentists between 2015 and 2017. AMU was quantified as the defined daily doses per 1,000 inhabitants per day (DID). The trends in dentist-prescribed AMU were examined according to antimicrobial category and administration route. We also compared outpatient oral AMU between dentists and physicians as well as between on-site and off-site dispensing. RESULTS: The DID values of dentist-prescribed AMU were 1.23 in 2015, 1.22 in 2016, and 1.21 in 2017. During this study period, outpatient oral antimicrobials comprised the majority (approximately 99%) of dentist-prescribed AMU, and cephalosporins were the most frequently prescribed antimicrobials (>60% of all antimicrobials). The DID values of outpatient oral AMU were 1.21 for dentists and 12.11 for physicians. The DID value for on-site dispensing was 0.89 in 2017, in which cephalosporins were the predominantly used antimicrobials (DID: 0.60). CONCLUSIONS: Interventions that target dentists in Japan should focus on on-site dispensing of oral antimicrobials (especially cephalosporins) for outpatients. Further studies are needed to ascertain the underlying factors of oral cephalosporin prescriptions to guide the development of effective antimicrobial stewardship programs.